Between Fight and Theatrical Performance: Conceptual Metaphors of Positionality in Communication about Cooperative Religious Education in Germany - Fabricius, Steffi (Religious education, 2022)
Whereas previous research has focused on religious education (RE), teachers’ religious attitudes, and personal religiosity, no studies to date have examined their experiences or discussion of positionality in a RE setting. The denominational-cooperative model of RE serves as a specific opportunity for such research since common denominational RE is a setting where denominational positionality seems to be an obvious factor beyond debate. Based on the analysis of RE teachers’ conversations on cooperative RE in Germany, the paper presents results of qualitative research into the conceptual metaphors of positionality and taking a position. In the analysis we found a consistent framing of experiences of positionality under three major conceptual metaphors with their source domains allocated to the semantic fields of motion, physical combat, and theatrical play. Since conceptual metaphors are assumed to stem from embodied experiences, to structure human thought, and can be found in language, the discussion of the data deals with the impression that these conceptual metaphors shape the RE teachers’ agency, i.e., the way they teach in the denominational-cooperative religious education classroom.